COVID-19, como factor de riesgo para parto pretérmino y rotura prematura de membrana en el Hospital Iquitos, año 2020 - Perea Perea, Ramses Salomon (2022)
This research seeks to determine if COVID-19 infection is a risk factor in the occurrence of preterm birth and premature rupture of membranes in pregnant women treated at the Iquitos Hospital during the months of April to December 2020. The design of the present study is of a non-experimental, observational, analytical and retrospective type of cases and controls, the data collection will be carried out from the clinical records of the Department of Gynecology and Obstetrics of the Iquitos Hospital. The data collection instrument will consist of 4 items: sociodemographic characteristics (age, marital status, level of education, occupation, Origin), Obstetric characteristics (prenatal control, parity, mode of delivery) independent variable (COVID 19 infection), dependent variables (preterm birth, premature rupture of the membrane). The study population will be made up of pregnant women who had preterm birth and premature rupture of the membrane in the obstetrics service of the Iquitos Hospital during the months of April to December 2020. The sample size corresponds to 70, of which the results will be taken. cases and controls will have a one-to-one relationship. The data collected will be processed by the statistical program IBM SPSS version 23 in Spanish, the Chi square test will be applied with statistical significance (p<0.05) and the Odds Ratio (OR) will be determined to determine the causal association between infection by COVID-19 in pregnancy with preterm birth and premature rupture of the membrane.